The analysis of promising directions for creation of domestic component base of volumetric rotary machines for low power energy, refrigeration and climate technology - V. L. Yusha; A. Yu. Gromov; Yu. A. Potapov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
An overview analysis of research and development in the field of volumetric rotary machines for low power energy, refrigeration and climate technology, as well as the state of the world and Russian market of compressor and expansion machines of this type is presented. It is shown that in this sector of domestic industry, the existing level and scale of production does not meet the requirements of ensuring the technological independence of the Russian Federation and the implementation of critical technologies. The analysis of the existing designs of rotary machines, as well as the nomenclature of domestic refrigeration and compressor engineering, allowed us to conclude that rotary machines of screw and spiral type are preferred for the implementation of existing licensed technologies at Russian enterprises. However, taking into account the urgency of ensuring import independence, rotary-plate compressor and expansion machines are of considerable interest. The prerequisites for improving the technical level and competitiveness of rotary-plate machines based on domestic technologies and new promising technical solutions are identified and formulated.